ДЕТЕКТИВЛИК ПРОЗАНЫҢ ЖАНРЛЫҚ ТӘБИЯТЫ - Матимов, К.Г. (FAN va JAMIYAT, 2025)
The article discusses the genre nature of detective prose. The artistic origins of this genre and its development in ancient and medieval times are revealed. The development of detective prose among fraternal peoples and the poetic achievements of detective prose in contemporary Karakalpak literature are noted.